A wearable textile dipole for search and rescue application - Ezzaty Faridah Nor, Mohd Hussin; Ping, Jack Soh; Mohamed Fareq, Abdul Malek; Mohd Faizal, Jamlos; Muhammad Ameerul Fikrey, Fauzi; H., Lago; Hasliza, A. Rahim (IEEE, 2017)
A wearable textile antenna for search and rescue application is presented in this work. It is designed based on the dipole topology to operate at 406 MHz for the Cospas-Sarsat application and fabricated fully using textile materials. The meanderline miniaturization technique is chosen to compact the proposed dipole due to its expected large size and wavelength at 406 MHz. The antenna evaluated in planar and bent forms indicated satisfactory performance when evaluated in terms of reflection coefficients, gain and radiation patterns.